You should write `(x-1)/(x+1) + (x+1)/(x-1)` as a mixed number that consists in a combination of a whole number and a proper fraction, such that:

`(x-1)/(x+1) + (x+1)/(x-1) = ((x-1)(x-1) + (x+1)(x+1))/((x-1)(x+1))`

`(x-1)/(x+1) + (x+1)/(x-1)= ((x-1)^2 + (x+1)^1)/(x^2-1)`

Expanding the binomials to numerator yields:

`(x-1)/(x+1) + (x+1)/(x-1) = (x^2-2x+1+x^2+2x+1)/(x^2-1)`

`(x-1)/(x+1)...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You should write `(x-1)/(x+1) + (x+1)/(x-1)` as a mixed number that consists in a combination of a whole number and a proper fraction, such that:

`(x-1)/(x+1) + (x+1)/(x-1) = ((x-1)(x-1) + (x+1)(x+1))/((x-1)(x+1))`

`(x-1)/(x+1) + (x+1)/(x-1)= ((x-1)^2 + (x+1)^1)/(x^2-1)`

Expanding the binomials to numerator yields:

`(x-1)/(x+1) + (x+1)/(x-1) = (x^2-2x+1+x^2+2x+1)/(x^2-1)`

`(x-1)/(x+1) + (x+1)/(x-1) = (2x^2+2)/(x^2-1)`

Factoring out 2 yields:

`(x-1)/(x+1) + (x+1)/(x-1) = 2(x^2+1)/(x^2-1)`

Hence, since the result is a mixed number, you may identify the whole number as `A = 2` , the numerator of the fraction `B = x^2+1` and the denominator `C = x^2-1`** .**

**Hence, converting the given expression in a mixed number yields that `B = x^2+1.` **